ACR Breast Density: Relationship with Age, and Its Impact on Mammographic and Ultrasound Findings - Wadyan Mustafa; Ola Mustafa (AlQalam Journal of Medical and Applied Sciences, 2024)
Breast cancer is a commonest cancer among women. Early detection by screening and diagnostic mammography could be reduced morbidity rate. ACR breast density is a risk factor in diagnosis of breast cancer in women whom have dense breast. ACR density mostly reduced with increasing age. A retrospective study carried on 222 female patients aged between 32-75 years with a mean 49 years, range 43 years, all patient subjected to mammography and complementary ultrasound, aimed to detect relation between ACR breast density and the age and the impact of ACR breast density on mammographic and ultrasound findings. Dense breasts (ACR d) seen only at younger age groups around 16 patients from 31-40 years age group and 14 patients from 41-50 years age group, the sensitivity and specificity of mammography in detection suspicious lesions in fatty breasts (ACR a) around 94.7% and 100 % respectively while the sensitivity and specificity of mammography in detection suspicious lesions in dense breasts (ACR c & d) were around 50% and 100 % respectively. ACR breast density usually has inverse relationship with the age, it could be reduced sensitivity of mammography in early detection of suspicious breast lesion especially in women have dense breasts, Addition of breast ultrasound as complementary imaging tool could be helpful in detection of occult mammographic lesions that could not detected in dense breasts. سرطان الثدي هو أكثر أنواع السرطان شيوعًا بين النساء. يمكن أن يؤدي الاكتشاف المبكر عن طريق الفحص والتصوير الشعاعي للثدي التشخيصي إلى تقليل معدل الإصابة بالمرض. تعد كثافة الثدي في ACR عامل خطر في تشخيص سرطان الثدي لدى النساء اللاتي لديهن ثدي كثيف. تنخفض كثافة ACR في الغالب مع تقدم العمر. أجريت دراسة بأثر رجعي على 222 مريضة تتراوح أعمارهن بين 32 و 75 عامًا بمتوسط 49 عامًا ونطاق 43 عامًا، وجميع المريضات خضعن للتصوير الشعاعي للثدي والموجات فوق الصوتية التكميلية، بهدف اكتشاف العلاقة بين كثافة الثدي في ACR والعمر وتأثير كثافة الثدي في ACR على نتائج التصوير الشعاعي للثدي والموجات فوق الصوتية. الثدي الكثيف (ACR d) يُرى فقط في الفئات العمرية الأصغر حوالي 16 مريضة من الفئة العمرية 31-40 عامًا و 14 مريضة من الفئة العمرية 41-50 عامًا، حساسية وخصوصية التصوير الشعاعي للثدي في الكشف عن الآفات المشبوهة في الثدي الدهني (ACR a) حوالي 94.7٪ و 100٪ على التوالي بينما كانت حساسية وخصوصية التصوير الشعاعي للثدي في الكشف عن الآفات المشبوهة في الثدي الكثيف (ACR c & d) حوالي 50٪ و 100٪ على التوالي. عادة ما يكون لكثافة الثدي في ACR علاقة عكسية مع العمر، يمكن تقليل حساسية التصوير الشعاعي للثدي في الكشف المبكر عن آفة الثدي المشبوهة خاصة عند النساء ذوات الثدي الكثيف، يمكن أن يكون إضافة الموجات فوق الصوتية للثدي كأداة تصوير تكميلية مفيدًا في الكشف عن الآفات الماموغرافية الخفية التي لا يمكن اكتشافها في الثدي الكثيف